Who produces knowledge? Transforming undergraduate students' views of science through participatory action research. Issue 6 (3rd June 2018) - Weinberg, Andrea E.; Trott, Carlie D.; Sample McMeeking, Laura B.
Abstract: Undergraduate research experiences (UREs) that include interdisciplinary, engagement‐oriented, and collaborative experiences have the potential to benefit students in unique ways. Through these innovative experiences, students are able to see the social impact and importance of their work—a factor known to strengthen the academic and career persistence of students traditionally underrepresented in science, technology, engineering, and mathematics (STEM) fields. In the present study, students assumed simultaneous roles as students, interdisciplinary researchers, and community liaisons as they facilitated a community‐engaged participatory research project. Using interpretive phenomenological analysis, we explore students' evolving perspectives of knowledge generation and social change processes before, during, and after the URE. Findings emphasize participants' altered views of the respective roles of academic researchers and community members in generating knowledge, the value of interdisciplinary research, and the potential of innovative UREs to foster positive change—in academic and community contexts.